Instant Powder of Lemongrass (Cymbopogon Citratus) on Dysmenorrhea Intensity in Adolescent - Harahap, hasanah Pratiwi; Nurrahmaton, Nurrahmaton; Zuiatna, Dian; Br. AP, Nuriah (Universitas Islam Jember, 2024)
Dysmenorrhea is a common disorder that often occurs before and during menstruation, characterized by pain and discomfort in the lower abdomen. The prevalence of primary dysmenorrhea experienced by teenagers in the first three years after menarche was 54.89%. It is very important to treat dysmenorrhea, this is because of the negative effects it has on teenagers due to enduring the pain, including fatigue and weakness and even nausea and vomiting because it can spread to the waist and thighs. Treatment that minimizes side effects can be done non-pharmacologically by using lemongrass, which containsantioxidants that reduce pain. This study aims to determine the effectiveness of instant lemongrass powder (Cymbopogon Citratus) on the intensity of dysmenorrhea in adolescents. The research used a PreExperimental Design with the form of One Group Pre-test and Post-test. The research population was76 teenagers using a purposive sampling technique, using inclusion and exclusion criteria according to the research of 16 teenagers. Dysmenorrhea intensity assessment used the NRS questionnaire. The data obtained was then carried out using the t test and obtained a value of Sig = 0.000 < 0.05, there was a significant impact in the form of changes in the intensity of dysmenorrhea in adolescents after administering instant lemongrass powder.